NILAI-NILAI KEARIFAN LOKAL DALAM BUDAYA PANTANG LARANG SUKU MELAYU SAMBAS - Aslan Aslan (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
Local wisdom is a cultural treasure owned by many ethnic groups in Indonesia today. Local wisdom is a shared value stemmed from society’s culture and used as a tool to control people in the community. Of many local wisdoms, Malay ethnic group has a unique prohibition or taboo, so-called pantang larang in Malay language. This culture constitutes as an ancestral heritage which is almost forgotten. It does not receive much attention from the society, including young generations who live in digital era. One of the possible reason is because parents do not tell local stories and advices. Consequently, the younger people do some negative behaviors since they do not comply the guidance of pantang larang and perceive it only as an old story. This paper, therefore, is a qualitative study which aims at describing the culture of pantang larang from Malay ethnic group.